FRI0046 Patients presenting with new musculoskeletal symptoms in the wrists, hands and feet enriches detection of anti-ccp antibodies in primary care – a national cohort study. (12th June 2018) - Pentony, P.; Karkalemis, K.; Nam, J.L.; Mankia, K.; Hunt, L.; Hensor, E.M.; Emery, P.
Abstract : Background: Selecting patients with new non-specific musculoskeletal complaints can enrich the prevalence of anti-cyclic citrullinated peptide (anti-CCP) antibodies compared with the general population. 1 Patients with rheumatoid arthritis (RA) frequently present with involvement of the wrist, hands and feet. Patients with elderly onset RA have a higher frequency of polymyalgic onset. However, it is unknown if elderly patients with shoulder complaints are more likely to be CCP positive. Objectives: To confirm the proportion of individuals with new-onset, non-specific MSK symptoms who were anti-CCP positive (CCP+) across a national cohort and investigate the initial presenting complaint of all individuals, as this may help determine whether there is a symptom complex that would prompt antibody testing. In addition to determine if the risk of being CCP +is increased in older patients presenting with shoulder symptoms. Methods: Individuals aged ≥18 years with new musculoskeletal complaints without synovitis from primary care were recruited prospectively. Participants completed a questionnaire on baseline musculoskeletal symptoms and provided a blood sample for anti-CCP antibody (Phadia CCP-2) testing. CCP+individuals where invited to attend follow-up in the rheumatology department, Leeds. The association between CCP status, smoking and shared epitope status was also assessed. Results: 4257 individuals were recruited, 2.9% (125/4257) were CCP+, a significantly higher proportion compared with the general population (1% (95% CI 2.4%>3.5% p<0.001)). Patients who presented with pain in the wrists, hands (RR 2.2 (1.5–2.9), p<0.001) or feet (RR 1.72 (1.2–2.4), p<0.001) had an increased relative risk of being CCP+. Patients who were older than 60 years who presented with shoulder symptoms (4.8% (7/146)) were no more likely to be CCP +than those who did not have shoulder symptoms (3.2% (31/1007), chi square p=0.313) and had the same prevalence of CCP +as those<60 years (3.5% (13/370), chi square p=0.461). A significantly higher proportion of ever smokers were CCP+ (14.2% (48/337)) compared with never smokers (3.3% (64/1926); chi square p<0.001). Ever smokers were also more likely than never smokers to be shared epitope positive in CCP +individuals (62.2% (23/37) cf 37.8% (14/37); p<0.007). Conclusions: Selecting individuals with new non-specific MSK symptoms without synovitis enriched the prevalence of anti-CCP positivity to 2.9%. Patients presenting with symptoms localising to the wrists, hands and feet were more likely to be CCP +which could prompt anti-CCP testing in these patients in primary care. Patients with shoulder complaints were no more likely to be CCP +than those without shoulder symptoms and had the same prevalence of CCP +as those<60 years. Reference: [1] Nam JL, et al., Enriching case selection for imminent RA: the use of anti-CCP antibodies in individuals with new non-specific musculoskeletal symptoms – a cohort study . Ann Rheum Dis, 2016;75(8):1452–6. Acknowledgements: The authors would like to thank all the participating general practitioners and health professionals and the UK Clinical Research Network teams for the referrals from primary care to the study Disclosure of Interest: None declared